Immigration and electoral support for the far-left and the far-right - Anthony Edo; Yvonne Giesing; Jonathan Öztunc; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Immigration is one of the most divisive political issues in the United States, the United Kingdom, France and several other Western countries. We estimate the impact of immigration on voting for far-left and far-right candidates in France, using panel data on presidential elections from 1988 to 2017. To derive causal estimates, we instrument more recent immigration flows by settlement patterns in 1968. We find that immigration increases support for far-right candidates. This is driven by low-educated immigrants from non-Western countries. We also find that immigration has a weak negative effect on support for far-left candidates, which could be explained by a reduced support for redistribution. We corroborate our analysis with a multinomial choice analysis using survey data.
Keywords: 330